Sistem Pendukung Keputusan Kelompok Promosi Jabatan Menggunakan Metode Fuzzy Profile Matching - Yudiana, I Made; Sugiartawan, Putu; Suprihanto, Didit (INFOTEKS (Information Technology, Computer and Sciences), 2021)
In a corporate organization, human resources are a very important element to support progress and quality in achieving the goals of the company. The most important thing that can be done by the company, namely the employee selection process, in order to guarantee the right candidate in the right position as well. In this study, we will discuss the methods that can be applied in the career path process in an organization. Problems that often occur, such as being difficult to determine the right person to fill a position, mistargeting in the promotion process, because it is only judged from several criteria, then promotions are less transparent and not objective. By implementing a group decision support system (SPKK), where the opinions of several decision makers can be accommodated, as well as in problem solving and communication occurs in a group. This study uses the profile matching method, because it can provide an assessment of the potential of each employee candidate by comparing the employee's personal profile with the profile of the position in question, combined with fuzzy logic so that the original value obtained by the alternative remains consistent from the beginning to the ranking process. The results obtained in the form of ranking reports using the borda method, based on calculations from the fuzzy profile matching method, are expected to help company organizations to facilitate the promotion process.